Clinical outcomes of endoscopic submucosal dissection for early gastric cancer in remnant stomach or gastric tube - Nishide, N.; Ono, H.; Kakushima, N.; Takizawa, K.; Tanaka, M.; Matsubayashi, H.; Yamaguchi, Y. (Endoscopy, 2012)
Background and study aims: Little information exists regarding the optimal treatment of early gastric cancer (EGC) in a remnant stomach or gastric tube. The aim of this study was to assess the feasibility and clinical outcomes of endoscopic submucosal dissection (ESD) for EGC in a remnant stomach and gastric tube.Patients and methods: Between September 2002 and December 2009, ESD was performed in 62 lesions in 59 patients with EGC in a remnant stomach (48 lesions) or gastric tube (14 lesions). Clinicopathological data were retrieved retrospectively to assess the en bloc resection rate, complications, and outcomes. Treatment results were assessed according to the indications for endoscopic resection, and were compared with those of ESD performed in a whole stomach during the same study period.Results: The en bloc resection rates for lesions within the standard and expanded indication were 100 % and 93 %, respectively. Postoperative bleeding occurred in five patients (8 %). The perforation rate was significantly higher (18 %, 11 /62) than that of ESD in a whole stomach (5 %, 69 /1479). Among the perforation cases, eight lesions involved the anastomotic site or stump line, and ulcerative changes were observed in five lesions. The 3-year overall survival rate was 85 %, with eight deaths due to other causes and no deaths from gastric cancer.Conclusion: A high en bloc resection rate was achieved by ESD for EGC in a remnant stomach or gastric tube; however, this procedure is still technically demanding due to the high complication rate of perforation.